PERENCANAAN PENDIDIKAN EKONOMI DAN BISNIS ISLAM DI DESA CIBITUNG TENGAH, KECAMATAN TENJOLAYA, BOGOR - Tubagus Rifqy Thantawi; Miftakhul Anwar; Eneng Kurniasih (SAHID DEVELOPMENT JOURNAL, 2022)
This community service aims to determine the extent of the role and at the same time practiceeducation and teaching of Islamic Economics and Business to the community in Cibitung TengahVillage, Tenjolaya District, Bogor. The role of education and education planning in IslamicEconomics and Business has become a reality and is increasingly widespread in Indonesiansociety along with the development of Islamic Economics and Business policies and practices.Therefore, the Faculty of Islamic Economics and Business, the Sahid Islamic Institute, Bogor, hasan interest in serving the community by practicing education and teaching in Islamic Economicsand Business. With this, people become more acquainted with, understand and practice thingsthat have been introduced and taught to them repeatedly, including the people in Cibitung TengahVillage, Tenjolaya District, Bogor.